Tingkat Stres dan Mekanisme Koping Mahasiswa dalam Penyusunan Skripsi pada Masa Pandemi - Ni Made Septyari; I Made Sudarma Adiputra; Ni Luh Putu Devhy (Universitas Baiturrahim, 2022)
The COVID-19 pandemic has spread in various countries, impacting various sectors. One of them is in the field of education, especially for final semester students who are preparing a thesis. Psychologically, the pandemic causes anxiety to stress among final year students. Previous research stated that 90.67% experienced physical symptoms of mild stress, 9.33% experienced physical symptoms of severe stress. Effective coping mechanisms are applied to create stressful conditions. This study aims to describe the level of stress and coping mechanisms of class XI students in the preparation of theses during the pandemic at STIKes Wira Medika Bali. The study used a quantitative descriptive design. Collecting data using a stress level questionnaire and coping mechanisms. The sample in this study was selected using a total sampling technique of 102 people. The results of the study showed that students' stress levels were categorized as moderate stress with a percentage of 51.0%, mild stress 32.4%, severe stress 9.8%, not experiencing stress 6.9%. Students have adaptive coping mechanisms with a percentage of 94.1% and maladaptive coping mechanisms 5.9%. The conclusion of this study is that most of the students' stress levels are in the moderate stress category and most students apply adaptive coping mechanisms